Expression of isocitrate dehydrogenase 1 and tumor protein 53 in high-grade glioma and its correlation with the outcome – A prospective study at a tertiary care center in India - Kumar, Vikas; Jaiswal, Pooja; Jaiswal, Somil; Tandon, Pradeep; Ojha, Bal Krishna (Asian Journal of Medical Sciences, 2024)
Background: Central nervous system tumors are the 10th most prevalent cause of mortality worldwide. The 2016 World Health Organization (WHO) classification of high grade gliomas (HGG) has identified Isocitrate dehydrogenase 1 (IDH 1) mutation as one of the primary molecular markers. Tumor protein 53 (p53) mutation is also closely associated with HGG. Aims and Objectives: The current study intended to ascertain the expression of IDH1 and P53 in patients with HGG and correlate that expression with clinical prognosis. Materials and Methods: The study included 34 patients with histopathological proven HGG. Relevant clinical information was recorded. The immunostaining results with anti-mouse monoclonal antibody for IDH 1 (R132H) and rabbit polyclonal antibody for p53 (RP 106-05) were statistically analyzed. Patients were followed up through telephone for a period of 1 year. Mortality within 1 year was regarded as a poor outcome. Results: About 85.29% (29/34) of the patients had Grade IV glioma, while only 14.71% (5/34) had Grade III glioma. Most patients with Grade III (3/5) (60.00%) and Grade IV (21/29) (72.41%) gliomas had p53 positivity. The majority of the patients with grade-III glioma (3/5) (60.00%) had IDH1 positivity, while most of the patients (23/29) (79.31%) with Grade IV gliomas had IDH1 negativity (P=0.0658). Age, gender, WHO grade, and adjuvant therapy did not show significant association with the outcome except for the p53 expression (P=0.0011*) and IDH1 expression (P=0.0025*). Correlation analysis showed a significant positive correlation between p53 makers with poor outcome (r=0.4781) and glioma grade (r=0.4028). Further, a negative yet insignificant correlation was recorded between IDH1 with age (r=−0.2285), p53 expression (r=−0.2568), and grade (r=−0.2988), although it showed a significant correlation with poor outcome (P=0.0001). Conclusion: p53-positive and IDH1-negative HGG had a significant correlation with the poor outcome. Thus, IDH1 and p53 are reliable markers for prognostication of HGG.